China: desaceleração do crescimento econômico e revisão do modelo - Eufrásio, Francisco Sidney Gomes (2016)
Over the past three decades, China excelled on the world stage, particularly, of its great economic growth. Structural reforms and economic opening initiated in 1978 transformed the economic structure of China, who ascended in the years 2000 to the condition of the world's second-largest economy. The international financial crisis of 2008, triggered by speculation in real estate, and drew attention to the shortcomings of Chinese growth model, based on high rates of internal investments and expanding exports. This growth strategy led the country to strong dependence on external demand which has highlighted the need for further structural reforms in the economy. Nevertheless, several measures have been taken by the Chinese Government in order to reorient the economy to a more sustainable growth model, focused on domestic demand. Household consumption and the expansion of the service sector should lead the economic growth of China in the coming years and should reduce dependence on external demand country.